(3OjhGf HgGA GdOjf RgjQs - (3GdHgGA RgjQ , RgjQ Hf eMeO Hf Ydj GdegdHj GdUGdMj, HgGA GdOjf,J (B656 (3g` s
(3ChdgG (B:s
(3CeG HYO abO SN dj Cf CPcQ aj gPg GdChQGb eG hbY dj ef GdJcde aj Ref GdTHGH Ydi MQha GdeYLe djSgd GdCeQ Ydi GdWdGH s
(3BNQgG (B:s
(3ef MQa GdjGA(B: (3CfG Ef eJ ef GdYTb Hg aHehJj ejJ GdYTGb Mj s
(3eQJHI MSH MQha GdgLGA cGdfSNI GdSGHbIs
(3fSNI KGfjIs
(3hQO CjVkG JMJ Qbe (B2202s
(3dcf JQJjH GdbUGFO eNJdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B52s
Keywords: (3GdCOHs